TABOO WORDS ON TIUR ANAK MEDAN™S INSTAGRAM VIDEO - Marbun, Lasria Sri Murniati; Andayani, Widya; Hasibuan, Juli Rachmadhani (Universitas Negeri Medan, 2020)
The study dealed with the taboo words used on Instagram video. The objectives of this study were to identify the types and the effect of taboo words uttered by tiur in his videos on Instagram. The sources of the data were taken from the videos of Tiur Anak Medan on Instagram. This is descriptive qualitative because this study focuses on the analysis of spoken language in social media. This study uses the theory of Batistella as the main theory which explain four types of taboo words, such as Epithets, Profanity, Obscenity and Vulgarity. After anylizing the data, there were 22 taboo words found in the videos. Ephitets was the most dominant taboo words found, then it was followed with obscenity which standed as the second types which the most found and the last vulgarity and profanity had the same number and the least found. Moreover, for the second analysis, It was found that the taboo words became the common words since they were used by the public figure. The taboo words were not the taboo anymore.